Students’ Acceptance and Enjoyment of ChatGPT in English Language Learning - Kartini, Made Marinety; Santosa, Made Hery; Indrayani, Luh (Journal of Educational Study, 2025)
The rapid growth of AI-based tools in education, particularly the increasing use of ChatGPT, has created an urgent need to understand how students perceive and engage with this technology to ensure its effective integration into English language learning. This research explores university students’ acceptance and enjoyment of using ChatGPT in English language learning among English Education students at Ganesha University of Education. The study employed a sequential explanatory mixed-methods approach. Quantitative data were collected through a survey consisting of 281 students, while qualitative data were collected from semi-structured interviews with 9 students selected through purposive sampling to capture more in-depth perspectives from active ChatGPT users. In the quantitative phase, students’ acceptance levels were examined using the modified Technology Acceptance Model (TAM) which included Perceived Usefulness, Perceived Ease of Use, Behavioral Intention, and Perceived Enjoyment. The results showed that students’ acceptance was categorized as high level, with an average score of 75.1, indicating that students generally accept ChatGPT as part of their English language learning. Qualitative results further revealed the psychological factors, particularly enjoyment, that significantly influenced students’ acceptance of ChatGPT. The students’ enjoyment was shaped by individual factors, learning environments, and the influence of lecturers. Overall, the findings highlight that students’ acceptance and enjoyment of ChatGPT are intertwined. Students’ willingness to integrate ChatGPT is also reinforced by positive and enjoyable learning experiences. These results suggest educators and institutions should design AI-assisted learning environments that are engaging, interactive and emotionally supportive. Creating such environments can enhance students’ technology adoption.